Optical Coherence Tomography of Van Der Waals Heterostructures Using Extreme Ultraviolet Light - Felix Wiesner; Johann J. Abel; Muhammad Hussain; Vipin Krishna; Alisson R. Cadore; Juan P. G. Felipe; Ana M. Valencia; Martin Wünsche; Julius Reinhard; Marco Gruenewald; Caterina Cocchi; Gerhard G. Paulus; et al. (Advanced Materials Interfaces)
Abstract New experimental methods with high out‐of‐plane spatial sensitivity combined with ultrafast temporal resolution can revolutionize the understanding of charge‐ and heat‐transfer dynamics occurring at interfaces. In this work, a step forward is taken in this direction by applying coherence tomography with extreme ultraviolet (EUV) light to different van der Waals heterostructures, which enables a 3D sample reconstruction with nanoscopic axial resolution. Furthermore, the measurements and, more in general, the approach is confirmed by ab initio calculations of the refractive index of layered materials that we compare to existing databases of empirical data. The EUV coherence tomography contrast is estimated in a broad spectral range (photon energy 65 –100 eV). This work sets the basis for the development of a new spectroscopy tool that, thanks to the temporal profile of EUV light sources and the high axial resolution of coherence tomography, can become the ideal probe of ultrafast processes occurring in van der Waals heterostructures and buried nanoscale opto‐electronic devices.